Gender Diversity dan Keahlian Keuangan Komite Audit dalam Memprediksi Financial Statement Fraud - Joko Prasetiyo; Puji Harto (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to examine the effect of audit committee attributes of gender and financial expertise on the ability to predict financial statement fraud. This research is a quantitative research using secondary data obtained through the Indonesian stock exchange. The subjects in this study were audit committees in transportation sector companies listed on the IDX. This study used a sample of 129 observations from 2019 to 2021. The census sampling method used in this study is that all populations fall into the sample category. Data analysis in this study used logistic regression analysis due to variable measurements using dummy. The results showed that gender diversity and financial expertise of the audit committee had a negative effect on detecting financial statement fraud partially, while simultaneously the variables gender diversity and financial expertise together had an effect on detecting financial statement fraud.